Constitutive Expression of Thermobifida fusca Thermostable Acetylxylan Esterase Gene in Pichia pastoris - Yang, Chao-Hsun (Molecular Diversity Preservation International (MDPI), 2010)
A gene encoding the thermostable acetylxylan esterase (AXE) in Thermobifida fusca NTU22 was amplified by PCR, sequenced and cloned into the Pichia pastoris X-33 host strain using the vector pGAPZαA, allowing constitutive expression and secretion of the protein. Recombinant expression resulted in high levels of extracellular AXE production, as high as 526 U/mL in the Hinton flask culture broth. The purified enzyme showed a single band at about 28 kDa by SDS-polyacrylamide gel electrophoresis after being treated with endo-β-N-acetylglycosaminidase H; this agrees with the predicted size based on the nucleotide sequence. About 70% of the original activity remained after heat treatment at 60 °C for three hours. The optimal pH and temperature of the purified enzyme were 8.0 and 60 °C, respectively. The properties of the purified AXE from the P. pastoris transformant are similar to those of the AXE from an E. coli transformant.